2007
DOI: 10.1021/ci7000378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Molecular Docking Programs for Virtual Screening

Abstract: Structure-based virtual screening is carried out using molecular docking programs. A number of such docking programs are currently available, and the selection of docking program is difficult without knowing the characteristics or performance of each program. In this study, the screening performances of three molecular docking programs, DOCK, AutoDock, and GOLD, were evaluated with 116 target proteins. The screening performances were validated using two novel standards, along with a traditional enrichment rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 20 publications
5
114
0
Order By: Relevance
“…Compared with the success rate using programs DOCK, AutoDock and GOLD, 15) shown in the table of Fig. 4b, the success rates of our ChooseLD program are almost equivalent to those of the docking program, GOLD.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Compared with the success rate using programs DOCK, AutoDock and GOLD, 15) shown in the table of Fig. 4b, the success rates of our ChooseLD program are almost equivalent to those of the docking program, GOLD.…”
Section: Resultsmentioning
confidence: 71%
“…The success rate of ChooseLD is compared with DOCK, AutoDock and GOLD. Corina 17) and MINI 15) show the method to determine initial ligand conformation. ChooseLD uses the furthest conformation from the experimental conformation.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that Dock shows an unexpectedly better screening performance in the enrichment rates, although each of these programs has a merit over others. 25 Therefore, Dock (https://dock.compbio.ucsf.edu/retrieve_ dock_distribution.html) is used in this study. Chimera tools are used to prepare the ligand (Wangzaozin A) and receptor structures for docking.…”
Section: Dockmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A variety of commercially or publicly available programs exist to enrich molecule databases, i.e., to select a fraction of the original database that is predicted to be enriched in potential ligands. 3,9 Docking programs rely on fast search algorithms to identify the best position of a potential ligand in the active site of a given target and to estimate the corresponding binding affinity using empirical scoring functions. 10 Modern high-performance computing (HPC) architectures, 11 which now extend to over 100,000 cores, open the door to massive VHTD of extremely large chemical databases by simultaneous use of a large number of processors, thus potentially increasing the probability of identifying potential new ligands against a variety of protein targets.…”
Section: Introductionmentioning
confidence: 99%